Once More with Feeling …the Art of Wooing the Public - Singapore Management University (Institutional Knowledge at Singapore Management University, 2013)
Public relations is an art, declares Rose Tan, the doyenne of Singapore’s own sports public relations industry. And although it’s changing rapidly as communications cross multiple platforms, it’s still something that needs to come from the heart.